Handbook of lean manufacturing in the food industry - Dudbridge, Mike (John Wiley & Sons Inc., 2011)
"Lean manufacturing is a system that helps to reduce costs while improving performance and output quality. This book presents the principles of lean manufacturing as they can be applied to food manufacturing. Other books on this topic are written at a higher level and tend to attempt to shoehorn the principles of the car and consumer electronics industries into places where they do not really fit. This is the first book to apply lean principles specifically in food industry settings, offering solutions which can alleviate pressures currently facing the industry."--Provided by publisher.